Long-term work outcomes and the efficacy of multidisciplinary rehabilitation programs on labor force participation in cancer patients - a protocol for a longitudinal prospective cohort study - Harald Engan; Line M. Oldervoll; Gro F. Bertheussen; Martine H. Gaarder; Roy A. Nielsen; Alain Paraponaris; Guro B. Stene; Jon A. Sandmæl; Torgrim Tandstad; Steffen Torp (SAGE Publishing, 2020)
Background. Many cancer survivors experience late effects of cancer treatment and therefore struggle to return to work. Norway provides rehabilitation programs to increase labor force participation for cancer survivors after treatment. However, the extent to which such programs affect labor force participation has not been appropriately assessed. This study aims to investigate i) labor force participation, sick leave and disability rates among cancer survivors up to 10 years after being diagnosed with cancer and identify comorbidities contributing to long-term sick leave or disability pensioning; ii) how type of cancer, treatment modalities, employment sectors and financial- and sociodemographic factors may influence labor force participation; ii) how participation in rehabilitation programs among cancer survivor affect the long-term labor force participation, the number of rehospitalizations and incidence of comorbidities. Design and methods. Information from four medical, welfare and occupational registries in Norway will be linked to information from 163,279 cancer cases (15.68 years old) registered in the Norwegian Cancer Registry from 2004 to 2016. The registries provide detailed information on disease characteristics, comorbidities, medical and surgical treatments, occupation, national insurance benefits and demographics over a 10-year period following a diagnosis of cancer. Expected impact of the study for Public Health. The study will provide important information on how treatment, rehabilitation and sociodemographic factors influence labor force participation among cancer survivors. Greater understanding of work-related risk factors and the influence of rehabilitation on work-participation may encourage informed decisions among cancer patients, healthcare and work professionals and service planners.